Freetown : Options for Growth and Resilience - World Bank Group (World Bank, Washington, DC, 2019)
Cities are where economic development really happens and where the risks from natural hazards are growing. Urbanization in Sierra Leone is occurring at USD 410/per capita, at a far lower level than other countries in Sub-Saharan Africa at similar urbanization levels. This study focuses on Freetown, the capital of Sierra Leone, that dominates the country’s urban landscape. A central premise of policy-making in cities is that the flexibility, practicality, and focus of local governments make them ideal players to understand and respond to the needs of their citizens. Indeed, cities mostly aim their problem-solving at local conditions. Freetown's population has increased roughly 10-fold in the last 50 years; similarly-sized European cities took 150 years to achieve this increase. Freetown's current economic and social infrastructure is dilapidated and basic service delivery has fallen short of population growth. Freetown is, and will likely remain, the most affected by the prevalent disasters in Sierra Leone, given its coastal location. Investments in capital and operational expenditures in the city are very low. Freetown is not an engine of service delivery, but neither is it an engine of growth for the country. Freetown lacks sufficient resources for much-needed investments in infrastructures and services necessary for its development. Policy choices made now will determine whether Freetown becomes an engine or an obstacle for economic transformation in Sierra Leone. Freetown is growing rapidly but is not delivering its potential. Purposeful and bold policy is needed from the incoming government. Similarly, in Sierra Leone changing current attitudes depends on building a credible account of how the future will be decidedly different. This has two parts. 1. Symbolic investments in the capital city can signal a future of productive investment and growth. 2. At the same time, supporting narratives allow citizens to understand that these symbols form part of a wider plan for the city and the country.For decades, Freetown has lacked such focused and purpose policies. The result of this prolonged neglect is visible to all: the city has become locked into low-productivity, is unprepared for natural hazards, and is increasingly a bottleneck to investment in the entire country. The new Government is a pivotal moment: a rare opportunity for smart new policies to transform Freetown into a platform for resilient growth. Freetown can become a city that works.